Pengaruh Good Corporate Governance Terhadap Pengungkapan Intellectual Capital Pada Industri Sub Sektor Advertising Printing Media Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022 - Fitri, Nadia; Handayani, Sri (Politeknik Negeri Ambon, 2024)
The aim of this research is to find empirical evidence about the relationship between good corporate governance and intellectual capital disclosure. The sample for this research was 19 industries using a saturated sampling method. The research population consists of the advertising, printing, and media subsector industries listed on the Indonesia Stock Exchange during the 2019-2022 period. The analysis was carried out using multiple linear regression, where the influencing (dependent) variable was limiting intellectual capital, and the influencing (independent) variables were institutional ownership, board of directors, board of commissioners, managerial ownership, and audit committee. The results of the analysis reveal that all of these independent variables have a positive impact on increasing intellectual capital. The partial test (ttest) found that institutional ownership, board of commissioners, and audit committee did not influence intellectual capital. Meanwhile, the board of directors and managerial ownership influence intellectual capital.